Algicidal activity synchronized with nitrogen removal by actinomycetes: Algicidal mechanism, stress response of algal cells, denitrification performance, and indigenous bacterial community co-occurrence - Ma, Ben; Li, Anyi; Chen, Shengnan; Guo, Honghong; Li, Nan; Pan, Sixuan; Chen, Kaige; Liu, Hanyan; Kosolapov, Dmitry B; Liu, Xiang; Zhi, Wei; Chen, Zhongbing; et al. (Journal of hazardous materials, 2024)
The harmful algal blooms (HABs) can damage the ecological equilibrium of aquatic ecosystems and threaten human health. The bio-degradation of algal by algicidal bacteria is an environmentally friendly and economical approach to control HABs. This study applied an aerobic denitrification synchronization algicidal strain Streptomyces sp. LJH-12-1 (L1) to control HABs. The cell-free filtrate of the strain L1 showed a great algolytic effect on bloom-forming cyanobacterium, Microcystis aeruginosa (M. aeruginosa). The optimal algicidal property of strain L1 was indirect light-dependent algicidal with an algicidal rate of 85.0%. The functional metabolism, light-trapping, light-transfer efficiency, the content of pigments, and inhibition of photosynthesis of M. aeruginosa decreased after the addition of the supernatant of the strain L1 due to oxidative stress. Moreover, 96.05% nitrate removal rate synchronized with algicidal activity was achieved with the strain L1. The relative abundance of N cycling functional genes significantly increased during the strain L1 effect on M. aeruginosa. The algicidal efficiency of the strain L1 in the raw water was 76.70% with nitrate removal efficiency of 81.4%. Overall, this study provides a novel route to apply bacterial strain with the property of denitrification coupled with algicidal activity in treating micro-polluted water bodies.
Keywords: Algicidal bacteria; dusík; Nitrates; Functional gene; Photosynthetic system; Denitrification; Harmful algal blooms; Photosynthesis; Harmful Algal Bloom; denitrifikace; Streptomyces; Bacterial and algal communities; fotosyntéza; Nitrogen; Microcystis; dusičnany; škodlivý vodní květ